Insect wing loss is tightly linked to the treeline: evidence from a diverse stonefly assemblage. Issue 4 (4th December 2018) - McCulloch, Graham A.; Foster, Brodie J.; Ingram, Travis; Waters, Jonathan M.
Abstract : The secondary loss of flight in previously winged insect lineages has long fascinated biologists. Habitat stability and isolation are thought to play important roles in driving wing reduction (Roff 1990, 1994), with exposure to high winds suggested to accelerate this process (Darwin 1859), although the role exposure plays in insect wing loss has never been empirically demonstrated. Here we assess fine‐scale distributional records from a diverse regional stonefly assemblage, to demonstrate a widespread association between wing loss and the treeline in New Zealand. The observed pattern suggests that exposure plays a crucial role driving wing loss in alpine insects.